Teknologi dalam Lingkup Pembelajaran Bahasa: Sebuah Kajian Bibliometrik Dari Tahun 2011-2020 - Nurhamidah, Restu; Sunarya, Dede Tatang; Julia, Julia (Jurnal Pena Ilmiah, 2021)
Learning is the core stage of education, one of the mandatory learning is language learning and the use of media such as technology are supporting tools during the learning process. The topics in this research are technology and language learning. This study aims to describe research journals indexed by Scopus in the period 2011-2020. This research was conducted in a systematic and structured manner through four stages: (1) searching for journal articles through Scopus metadata using Publish or Perish software; (2) filtering journal articles from Scopus metadata; (3) checking and finalizing journal article metadata; (4) doing bibliometric analysis using VOSviewers software. There are four findings of the analysis; (1) the development of journal publications on technology in the scope of language learning; (2) collaboration of authors of journal publications on technology in the scope of language learning; (3) the trend of terms in key journals about technology in the scope of language learning; (4) the trend of terms in journal abstracts about technology in the scope of language learning.